Genetics of Subclinical Coronary Atherosclerosis - Bielak, Lawrence F. (Curr Genet Med Rep, 2018)
PURPOSE OF REVIEW. This review highlights recent findings regarding genetics of coronary artery calcification (CAC), a marker of subclinical atherosclerosis burden, that is a precursor of clinical coronary artery disease. RECENT FINDINGS. CAC quantity is heritable. Genome wide association studies of common single nucleotide polymorphisms have identified genomic regions explaining ~2.4% of CAC heritability. Low frequency and rare variants explain additional variation in CAC. Evidence suggests that there may be different genetic etiologies for variation in CAC progression than for cross-sectional measures of CAC. Studies integrating multiple -omics data are providing new insights into the pathobiology of subclinical coronary atherosclerosis. SUMMARY. The future is promising for innovative studies utilizing whole genome sequencing data as well as other -omics such as epigenomic modifications of genes and gene expression. These studies may provide multiple sources of data pointing to the same gene or pathway, thus providing greater confidence in findings.